Obligatory metabolomic profiling of gene‐edited crops is risk disproportionate. (20th July 2020) - Fedorova, Maria; Herman, Rod A.
SUMMARY: It has been argued that the application of metabolomics to gene‐edited crops would present value in three areas: (i) the detection of gene‐edited crops; (ii) the characterization of unexpected changes that might affect safety; and (iii) building on the track record of rigorous government regulation in supporting consumer acceptance of genetically modified organisms (GMOs). Here, we offer a different perspective, relative to each of these areas: (i) metabolomics is unable to differentiate whether a mutation has resulted from gene editing or from traditional breeding techniques; (ii) it is risk‐disproportionate to apply metabolomics for regulatory purposes to search for possible compositional differences within crops developed using the least likely technique to generate unexpected compositional changes; and (iii) onerous regulations for genetically engineered crops have only contributed to unwarranted public fears, and repeating this approach for gene‐edited crops is unlikely to result in a different outcome. It is also suggested that article proposing the utility of specific analytical techniques to support risk assessment would benefit from the input of scientists with subject matter expertise in risk assessment. Significance Statement: The promise of gene editing for improving crops and sustainable agriculture is contingent on its broad availability to plant breeders via the avoidance of risk‐disproportionate regulations that have severely limited the use of GMOs. Gene editing should be placed in the context of other plant breeding methods, and risk assessment should proceed according to sound risk‐assessment principles and should be proportional to plausible risks, rather than being driven by the availability of specific technologies for assessing negligible risks.